Estimating obstetric and gynecologic surgical rate: A benchmark of surgical capacity building in Ghana. Issue 2 (22nd November 2019) - Gyedu, Adam; Lester, Lynette; Stewart, Barclay; Danso, Kwabena A.; Salia, Emmanuella L.; Quansah, Robert; Donkor, Peter; Mock, Charles
Abstract: Objective: To estimate the annual rate of obstetric and gynecologic (ObGyn) operations performed in Ghana and establish a baseline for tracking the expansion of Ghana's surgical capacity. Methods: Data were obtained for ObGyn operations performed in Ghana between 2014 and 2015 from a nationally representative sample of hospitals and scaled up for national estimates. Operations were classified as "essential" or "other" according to The World Bank's Disease Control Priorities Project. Data were used to calculate cesarean‐to‐total‐operation ratio (CTR) and estimate the rate of cesarean deliveries based on the number of live births in 2014. Results: A total of 90 044 (95% uncertainty interval [UI] 69 461–110 628) ObGyn operations were performed nationally over the 1‐year period, yielding an annual national ObGyn operation rate of 881/100 000 females aged 12 years and over (95% UI 679–1082). Eighty‐seven percent were essential procedures, 80% of which were cesarean deliveries. District hospitals performed 71% of ObGyn operations. The national rate of cesarean deliveries was 7.2% and the CTR was 0.27. Conclusion: The cesarean delivery rate of 7.2% suggests inadequate access to obstetric care. The CTR of 0.27 suggests inadequate overall surgical capacity. These measures, along with estimates of distribution of procedures by hospital level, provide useful baseline data to support surgical capacity building efforts in Ghana and similar countries. Abstract : Ghana's cesarean rate of 7.2% suggests inadequate access to obstetric care while its cesarean to total operation ratio of 0.27 suggests inadequate overall surgical capacity.